MiR-21 Reduces Hydrogen Peroxide-Induced Apoptosis in c-kit+ Cardiac Stem Cells In Vitro through PTEN/PI3K/Akt Signaling. (10th October 2016) - Deng, Wenwen; Wang, Yan; Long, Xianping; Zhao, Ranzun; Wang, Zhenglong; Liu, Zhijiang; Cao, Song; Shi, Bei
Abstract : The low survival rate of cardiac stem cells (CSCs) in the infarcted myocardium hampers cell therapy for ischemic cardiomyopathy. MicroRNA-21 (miR-21) and one of its target proteins, PTEN, contribute to the survival and proliferation of many cell types, but their prosurvival effects in c-kit + CSC remain unclear. Thus, we hypothesized that miR-21 reduces hydrogen peroxide- (H2 O2 -) induced apoptosis in c-kit + CSC and estimated the contribution of PTEN/PI3K/Akt signaling to this oxidative circumstance. miR-21 mimics efficiently reduced H2 O2 -induced apoptosis in c-kit + CSC, as evidenced by the downregulation of the proapoptosis proteins caspase-3 and Bax and upregulation of the antiapoptotic Bcl-2. In addition, the gain of function of miR-21 in c-kit + CSC downregulated the protein level of PTEN although its mRNA level changed slightly; in the meantime, miR-21 overexpression also increased phospho-Akt (p-Akt). The antiapoptotic effects of miR-21 were comparable with Phen (bpV), the selective inhibitor of PTEN, while miR-21 inhibitor or PI3K's inhibitor LY294002 efficiently attenuated the antiapoptotic effect of miR-21. Taken together, these results indicate that the anti-H2 O2 -induced apoptosis effect of miR-21 in c-kit + CSC is contributed by PTEN/PI3K/Akt signaling. miR-21 could be a potential molecule to facilitate the c-kit + CSC therapy in ischemic myocardium.